Pollution Of The Marine Environment In The Southeast Asian Region In The Perspective Of International Environmental Law - L.ya Esty Pratiwi; Achmad Hariri; Levina Yustitianingtyas (Universitas Islam Darul Ulum, 2025)
Marine environmental pollution has emerged as a critical issue in Southeast Asia, a region known for its rich marine biodiversity, strategic maritime routes, and rapid economic development. The combination of dense maritime traffic, industrial expansion, and inadequate regulatory enforcement has intensified the vulnerability of this region to marine pollution, including oil spills, plastic waste, and chemical discharge. This paper examines the legal framework governing marine environmental protection under international environmental law, with a particular emphasis on its application and enforcement in Southeast Asia.The study analyzes key international conventions such as the United Nations Convention on the Law of the Sea (UNCLOS) 1982, the International Convention for the Prevention of Pollution from Ships (MARPOL 73/78), the London Dumping Convention 1972, the Oil Pollution Preparedness, Response and Cooperation Convention (OPRC) 1990, and the International Convention on Civil Liability for Oil Pollution Damage (CLC) 1969. These instruments are critically reviewed in terms of their relevance, ratification status, and domestic implementation across Southeast Asian countries. Using a normative research methodology, this paper is supported by a case study of the Montara oil spill in the Timor Sea, which significantly impacted Indonesia’s marine ecosystem and highlighted deficiencies in cross-border environmental governance. The study underscores the shared responsibility of both state and non-state actors in preventing and mitigating marine pollution and stresses the urgent need for enhanced regional cooperation, legal harmonization, and institutional capacity-building. Despite the presence of robust international legal frameworks, challenges persist in enforcement due to legal fragmentation, technical limitations, and political sensitivities. This paper recommendas strengthening regional legal instruments, improving state compliance, and fostering collaborative mechanisms to ensure sustainable marine environmental governance in Southeast Asia.